ENT 530 Social Media Portfolio: Epodise / Wan Nuratirah Che Ab Ghani - Che Ab Ghani, Wan Nuratirah (2021)
The portfolio will explain on the progress of Epodise. Epodise is a clothing brand business that operate as online using the Facebook (FB) as their platform to operate their business. Epodise focus on teenager and adult female clothing for different style and size. The Facebook page was first created on November 2020 by the founder, Wan Nuratirah binti Che Ab Ghani. The mission and vision of the clothing brand are stated as to enhance the beauty and style so that they can confidently say they ‘Look Great’ and to be the best clothing brand that offer high quality, design and service to our customer respectively. In the Facebook page, teaser, soft sell such as tips how to be more stylish, how to match colours, how to look taller and more are posted to attract customer in checking page for more information before hard sell are posted.